FLORAL DIVERSITY, SOIL PROPERTIES, AND BIOMASS DISTRIBUTION IN NATURAL, RIPARIAN AND PLANTATION FOREST ECOSYSTEMS IN EJIGBO, OSUN STATE, NIGERIA - Agwu, O. P.; Bolanle-Ojo, O. T.; Onefeli, A. O.; Aderibigbe, A. A.; Ugbong, E. A.; Azeez, U. A.; Idowo, A. E.; Amujo, O. A.; Funmilayo, A. D.; Olaniyan, D. (RENEWABLE, 2026)
The assessment of biomass distribution, floral diversity and soil characteristics could assist ecosystem managers in the conservation of tropical ecological landscapes and enhance ecosystem function. This study investigated the floral diversity and biomass distribution in natural, riparian and plantation forest ecosystems in Ejigbo, Osun State, Nigeria. Growth variables such as diameter at breast height, total height, crown dynamics, and above and below-ground biomass were assessed. Diversity indices were computed, and the above and below-ground biomass were estimated using an allometric equation. A total of 116 plant species belonging to different life forms (trees, shrubs, herbs, and climbers) were identified. Riparian forests had higher tree species composition than natural forests, but the natural forest was more diverse. The organic carbon content in riparian forest soil was higher (37.8%) than in natural forest (29.07%). Riparian forest soil was less acidic (pH: 6.65) compared to the natural forest (6.47). The conservation and management of these habitats are critical for the mitigation of climate change and the maintenance of ecosystem services.